Rheumatoid arthritis and the intestinal microbiome: probiotics as a potential therapy - Yang, Yang; Hong, Qing; Zhang, Xuehong; Liu, Zhenmin (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a systemic autoimmune disorder characterized by swollen joints, discomfort, stiffness, osteoporosis and reduced functionality. Genetic, smoking, dust inhalation, high BMI, hormona and gut microbiota dysbiosis are all likely causes of the onset or development of RA, but the underlying mechanism remains unknown. Compared to healthy controls, patients with RA have a significantly different composition of gut microbiota. It is well known that the human gut microbiota plays a key role in the initiation, maintenance and operation of the host immune system. Gut microbiota dysbiosis has local or systematic adverse effects on the host immune system, resulting in host susceptibility to various diseases, including RA. Studies on the intestinal microbiota modulation and immunomodulatory properties of probiotics have been reported, in order to identify their potential possibility in prevention and disease activity control of RA. This review summarized current studies that the role and potential mechanisms of gut microbiota in the development and progression of RA, as well as the preventative and therapeutic effects and potential mechanisms of probiotics on RA. Additionally, we proposed the challenges and difficulties in the application of probiotics in RA, providing the direction for the research and application of probiotics in the prevention of RA.